Human papillomavirus detection and typing: recent progress and clinical perspectdes - Bigio, Cecília T.; Barboza, Fabiano A.; Cavalcanti, Silvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
The molecular biology and related lechnologies had made impressive advances in the last decades. diffcrently from routine optical microscopy. The contribution of those recent DNA tests to the detection of HPV in screening female low grade lesions and inconclusive diagnosis in cervical smears are valious, improving clinical management. The large scale use of H PV tesl still needs prospective studies evaluating greater populalions of clinical routine. It is worth to expect that the new data will clarify the usefulness f HPV detection in screening câncer precursors, contributing in diagnostic screening of patients at higher risk for câncer and to help in improve citopathology as a quality control.